PENGARUH EKSTRAK BUAH BELIMBING WULUH (AVERRHOA BILIMBI L.) TERHADAP DAYA TETAS TELUR IKAN GURAMI: Effectiveness Of Belimbing Wuluh’s Ektrack (Averrhoa Bilimbi L.) On Hatchability Of Carp Eggs Gouramy - Sugiman, Sugiman; Liliyanti, Mita Ayu; Artiningrum, Novita Tri; Nufus, Chairun (Yayasan Al-Amin Qalbu, 2024)
Carp is one of commodities freshwater many developed by the cultivator of the fish, as the demand for a high market, maintenance easy and princes relatively stable, think nice and nutrition content high. One alternative to address the problem is the use of extract fruit carambola wuluh. Of which it has infected a fungus saprolegnia sp. Marinated to extrac the fruit of the leatherback wuluh. The concentration of an extract to the leatherback wuluh that is used is identification ppm 4.000 to the density of the 50 egg. The research uses the experimental methods random design it is the complete (RAL) with 4 treatment and 3 preparation of test questions so that apol corporate secretary ronald naggol there were a total of 12 of the experiment. Treatment P1 (time of soaking 10 minutes), treatment P2 (time of soaking 15 minutes), treatment P3 (time of soaking 20 minutes), treatment P4 (in the absence of soaking / control). The research results show that the addition of an extract the fruit of the leatherback wuluh to exert an influence real (P<0,05) against hatch power has risen and other eggs and concern only the survival of roasted gouramy fish with a long time of soaking an extract the fruit of the leatherback wuluh as longaudience with the value of hatch power has risen and other eggs as much as (96.67%). and the level of concern only the survival of (97.93%)